Criminal Mediation in Polish and Bosnian Legislation – Similarities, Differences, and Challenges in the 21st Century - Skrobotowicz, Grzegorz Adam; Kazić-Çakar, Ena (Review of European and Comparative Law, 2023)
Worldwide, mediation is one of the most used mechanisms of alternative dispute resolution across many fields of law and one of the most common forms of restorative justice. Although it brings advantages to criminal law, some criticize its potential application for certain types of crimes. However, its benefits seen through effectiveness, efficiency in reaching conflict solutions, and the positive impact on victims and perpetrators are irrefutable. Having that in mind, this article aims to conduct comparative research, discuss the functioning of mediation in criminal cases in Polish and Bosnian criminal law and present similarities and differences between their legal regulations.